Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pengunjung Hotel - Irena Larashati (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2019)
Competition in the business world today is increasingly competitive; this is also felt by business people in the hospitality sector who demanded to have better service quality and reasonable prices to satisfy customer satisfaction. This study aims to determine the effect of service quality and price on hotel visitor satisfaction. The analysis used in this study is verification analysis with path analysis. I am using a sample of visitors at one of the 3-star hotels in the city of Bandung as many as 99 visitors. The results showed that there was an influence of service quality and price on visitor satisfaction by 0.77.1%, while the remaining 22.9% was influenced by other factors not examined.